Temperature dependence of the mechanical behaviour of praesodymium phosphate glasses - Budi, Agus Setyo; Ayob, Mohd Nizam; Ahmad, Asmala; Lau, K.T. (Malaysian Solid State Science and Technology Society (MASS), 2006)
Longitudinal and shear ultrasonic velocities were measured in different compositions of the glass system xPr6O11 (1-x) P2O5 at temperature range between 270 K and 323 K. From the transit time data and density, we found that all the mechanical behaviour of these glasses decreases as the Pr6O11 content increases, which indicates a weakening of the binding energy in the network.